Prisoners of Britain : German civilian and combatant internees during the First World War - Panayi, Panikos (Book collections on Project MUSE., 2012)
During the First World War hundreds of thousands of Germans faced incarceration in hundreds of camps on the British mainland. This is the first book on these German prisoners, almost a century after the conflict. The book covers the three different types of internees in Britain in the form of: civilians already present in the country in August 1914; civilians brought to Britain from all over the world; and combatants. Using a vast range of contemporary British and German sources the volume traces life experiences through initial arrest and capture to life behind barbed wire to return to Germany or to the remnants of the ethnically cleansed German community in Britain. The book will prove essential reading for anyone interested in the history of prisoners of war or the First World War and will also appeal to scholars and students of twentieth-century Europe and the human consequences of war.